Analysis of Lecturers' Abilities in Preparing Pai Cluster Rps: A Critical Discourse Analysis (Cda) Study - Devi Indah Sari; Maryam Lubis; Muhammad Fadhli Azmi; Siti Halimah (Britain International of Humanities and Social Sciences (BIoHS) Journal, 2026)
The implementation of Outcome-Based Education (OBE) in higher education requires reform in the governance of learning tools, especially Semester Learning Plans (RPS). This document is not merely an administrative file but a discursive representation of lecturers' pedagogical ideology. This study aims to analyze lecturers' abilities in formulating Graduate Learning Outcomes (CPL), Course Learning Outcomes (CPMK), Sub-CPMK, the depth of study materials, learning methods, evaluation indicators, and the alignment of weekly plan tables in the Islamic Religious Education (PAI) course group. The method used is Norman Fairclough's three-dimensional Critical Discourse Analysis (CDA) model that integrates lexicogrammatical text analysis, discursive practices (document production and consumption), and socio-cultural practices within academic institutions. Data sourced from the RPS documents of the PAI Learning Strategy, PAI Learning Evaluation, and Al-Qur'an courses in the PAI Study Program, reinforced by in-depth interviews with the lecturers. The analysis results show the dominance of technocratic-procedural vocabulary (procedural knowledge) compared to reflective-transformative vocabulary (metacognitive knowledge). Most of the formulation of achievement and evaluation instruments are still trapped in the lower cognitive realm (C2-C3) and are normative-formalistic in nature to fulfill accreditation regulations and campus bureaucracy. Institutional power relations are proven to limit the space for lecturer creativity due to the standardization of rigid templates. This research provides a novel contribution in the form of deconstruction of the academic language of the RPS document, exposing the discursive tension between the maintenance of traditional moral-religious orthodoxy and the demands of critical and transformative 21st-century competencies.